Pengaruh Pola Makan dengan Kejadian Gastritis - Azahra Nasywa Putri Farisa; Febriana Rachmawati; Febri Nur Hidayah; Hasna Aufa Rafiqi; Nabilah Yasin (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
According to Dermawan D & Rahyuningsih, T (2010), gastritis is not a single disease, but several conditions that refer to stomach inflammation. Usually this inflammation is the result of a bacterial infection which can cause stomach ulcers, namely Helicobacter Pylory and is the only bacteria that lives in the stomach. Unhealthy lifestyles such as consuming foods that can stimulate an increase in stomach acid, such as pickles, vinegar, chili sauce, as well as smoking and drinking alcohol, can increase the number of gastritis sufferers. Gastritis is one of the most common digestive tract health problems. The aim is to find out risk factors regarding the influence of irregular eating patterns. Method The type of research used is descriptive analytical observational. The approach method used is a cross sectional approach, which is research to study the dynamics of the correlation between risk factors and effects, by approaching, observing or collecting data at one time (point time approach). (Notoatmodjo, 2010). Research findings found that the majority of female respondents showed poor eating patterns. Implications: Knowledge of gastritis risk factors is very important to form a healthy eating pattern, which has an impact on stomach health.